Perancangan Aplikasi Manajemen Surat Menyurat Untuk Pengelolaan Informasi Administrasi Kependudukan - Mariana Purba; Erlangga; Marissa Utami; Nia Umilizah; Lemi Iryani (LPPMPP Yayasan Sejahtera Bersama Bengkulu, 2024)
The purpose of this study is to develop a web-based application system to improve the management of population administration information letters, especially the processing of citizen data, especially in the process of making birth certificates, death certificates, cover letters, and other letters. The case study of this research is the Babatan Saudagar Village Office, Peoral District, Ogan Ilir District, South Sumatra with the time this research was conducted from December 2020 to June 2021. In this study, to obtain and collect data in accordance with the needs of the system, interview and observation methods were used. This system can automate the archiving of incoming and outgoing mail data, replacing manual methods and improving accuracy. The creation of this village correspondence service application is believed to be able to overcome the obstacles that occur in the manual service system that is currently used.